Deceased donor uterus transplantation: religious perceptions - Pittman, Jana; Gerstl, Brigitte; Cavazzoni, Elena; Rogers, Natasha Mireille; Lotz, Mianna; Deans, Rebecca (Frontiers in Transplantation, 2025)
BackgroundUterus transplant now offers an alternative deceased donation treatment option for women with uterine infertility. Limited research exists on religious opinions that may impact the addition of the uterus to current multi-organ deceased donor programsObjectiveTo explore the acceptability of uterus transplantation and deceased uterus donation across different religious groups.DesignA cross-sectional survey of 2,497 participants was conducted between October 2022 and January 2023 in NSW Australia. Australia is a culturally and religiously diverse nation with over 60% of people identifying with a religion, including Christianity (43%), Islam (3.2%), Buddhism (2.7%), Hinduism (2.4%). This survey captured awareness and attitudes towards deceased uterus donation. Descriptive statistics and regression analyses were used to explore factors influencing organ donation and next-of-kin perceptions.ResultsA total of 2,497 respondents completed the survey. Christians had greater awareness of organ donation but were less likely to be registered donors, or consent to uterus donation. Those of Hindu faith were less likely to be registered organ donors. Next-of-kin from the Islamic faith were reluctant to consent to organ donation if the donor's pre-death wishes were unknown, and less likely to consent to uterus donation. Participants identifying as Buddhist had a higher awareness of uterus transplantation.ConclusionOrgan donor awareness and consent rates varied across religious groups, including for uterus donation. Differences may stem from varying beliefs about bodily integrity, and reproductive rights, which may influence attitudes toward uterus donation. Tailored culturally and linguistically sensitive educational campaigns should address the unique aspects of uterus donation.